Experimental measurements of two elastic taut-slack mooring configurations for the multi-float M4 WEC (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Moorings are a vital and often problematic component of any floating offshore renewable energy system, whether for wind or wave energy conversion, and here we consider the multi-float WEC system M4 in a 122 configuration. Previous experimental work has shown elastic cables to reduce extreme snap loads by a factor of about 6 when considering single cables between the bow float and a mooring buoy, and between the mooring buoy and the bed [1]. Here we compare results for two alternative configurations designed to reduce the mooring footprint as well as extreme snap loads. The first system, shown in Figure 1 (a), consists of a large surface buoy connected to the seabed with three equi-spaced elastic cables in pre-tension, with a single elastic cable to the bow float. The second system, shown in Figure 1 (b) has a smaller submerged buoy, again connected to the seabed with three equi-spaced elastic cables in pre-tension, however, this is connected to a smaller surface buoy which is subsequently connected to the bow float. Both systems are taut-slack. In this paper we present experimental measurements taken at the COAST laboratory at the University of Plymouth. Both configurations are tested in irregular (JONSWAP) wave conditions up to limiting steepness, with run times of 35 mins at 1:40 scale or about 3.5 hours full scale. Peak, mean and rms bed loads for both configurations are presented along with rms and peak relative angular pitch response with drive train disengaged (free hinge between mid and stern floats).References[1] P. Stansby et al., “Experimental study of mooring forces on the multi-float WEC M4 in large waves with buoy and elastic cables,” Ocean Eng., vol. 266, no. P4, p. 113049, 2022.